Terrorists on Trial A Performative Perspective - de Graaf, Beatrice; Schmid, Alex P. (Leiden University Press, 2016)
Terrorism trials are an exceptional opportunity for better understanding and, hence, countering terrorism, since they are often the only place where most if not all of the actors of a terrorist incident meet again, and where the media report and broadcast their respective accounts. Seeing terrorism trials as a stage where legal instruments are used (and abused) to argue the validity of contested political constructs, this study presents a performative perspective to draw attention to the mechanisms and effects of terrorism trials in and outside the courtroom. With a special focus on how the power of these performances may in turn shape new narratives of justice and/or injustice, it offers vital insights into terrorism trials directed involving different types of terrorism suspects, from left-wing to ethno-nationalist and jihadist terrorists, in Spain, Russia, Germany, the Netherlands, and the US.